Ragam Bahasa Presenter Infotainment â€œKISSâ€ di Stasiun Televisi Indosiar - Andriani, Tika; Arief, Ermawati; Nursaid, Nursaid (Universitas Negeri Padang, 2012)
The article aims to describe the use of different languagesâ€‹â€‹ by presenter infotainment Indosiar terms of accuracy and suitability choice of words. The research datais an extract speech language diversity in the television presenter infotainment KISS Indosiar, while that will be thesource ofthe data is KISS on television infotainment Indosiar. Data collected by recording technique andrecord engineering. The findings ofthe studyare, (1) variety of languageused by the presenter infotainment KISS in Indosiar are various casual, (2) appropriate selection of words seen by the useof synonyms, words of his own creation, and foreign words, (3) the suitability of the choice of words seen by the use of popular words, words of jargon and slang words.